Societal well-being and resource use - Ugur Soytas; Ramazan Sari (Humanities & Social Sciences Communications)
Abstract A production function defines the link between economic output and consumption of resources. However, our knowledge of how societal well-being is linked to resource use is limited. The current research predominantly emphasizes a diminishing contribution of energy use to well-being across all countries, indicating a non-linear saturation function. In this paper, an argument is made for an S-shaped association of societal well-being to resource use more broadly. The variations in the roles of hedonic and eudaimonic well-being dimensions explain the S curve. At low levels of resource use, the hedonic dimension leads to an exponential increase in well-being. When short-run needs are met, well-being contributions of resource use start declining. After this inflection point, we argue that the eudaimonic dimension starts dominating. The knee point of the S refers to the level after which contributions to well-being become negligible. Based on these turning points, fair and subsistence use levels are introduced as innovative social boundaries of resource consumption. Without imposing any functional form, the kernel estimates between Human Development Indexes and material footprints support the S-shape conjecture, with slight deviations for biomass, fossil fuel, metal, and mineral footprints. We argue that, as expected, well-being can decline when environmental impacts of excessive resource use are considered.